Implementing Panic-Focused Psychodynamic Psychotherapy into Clinical Practice. (June 2013) - Beutel, Manfred E; Scheurich, Vera; Knebel, Achim; Michal, Matthias; Wiltink, Jörg; Graf-Morgenstern, Mechthild; Tschan, Regine; Milrod, Barbara; Wellek, Stefan; Subic-Wrana, Claudia
Objective: To determine the effectiveness of manualized panic-focused psychodynamic psychotherapy (PFPP) in routine care in Germany. Method: German psychoanalysts were trained according to the PFPP manual. Fifty-four consecutive outpatients with panic disorder (with or without agoraphobia) were randomly assigned in a 2:1 ratio to PFPP or cognitive-behavioural therapy (CBT) plus exposure therapy. Subjects (female 57.4%; mean age 36.2 years) had high rates of psychiatric (68.5%) and somatic (64.8%) comorbidity, and previous psychiatric treatments (57.4%). Assessments were performed pre- and posttreatment and at 6-month follow-up. The primary outcome measure was the Panic Disorder Severity Scale. Results: Both treatments were highly effective. In patients randomized to PFPP, remission was achieved in 44.4% at termination and by 50% at follow-up (CBT 61.1 % and 55.6%, respectively). No significant differences were found. Emotional awareness, a posited moderator of good outcome in psychotherapies, was significantly higher in the CBT group at baseline. It was found to be a strong moderator of treatment effectiveness in both treatments. After adjusting for initial Levels of Emotional Awareness Scale (LEAS) scores, effect sizes (ESs) for the primary outcome were Cohen d = 1.28, from pre- to posttreatment, and d = 1.03, from pretreatment to follow-up, for PFPP, and d = 1.81 and 1.28 for CBT, respectively. Conclusions: PFPP was implemented effectively into clinical practice by psychoanalysts in the community in a sample with severe mental illness with large ESs. Assessment of LEAS may facilitate the identification of patients suitable for short-term psychotherapy. (Clinical Trial Registration Number: German Clinical Trials Register, DRKS00000245; Universal Trial Number, U1111-1112-4245)